Implementation Autocad® Civil 3D for Horizontal Alignment Design of Indramayu-Jatibarang Highways - Stefanus, Stefanus; Rifai, Andri Irfan; Nasrun, Nasrun (DAS Institute, 2022)
The geometric planning of the road has been made more convenient by technological advances in construction, which have led to innovations that are still growing. With the use of Autocad® Civil 3D, the process of planning the Indramayu-Jatibarang roadways is complete. This paper aims to explain how to plan roadways geometrically with Autocad® Civil 3D and to provide the reader a knowledge of how Autocad® Civil 3D can speed up and simplify work processes. The approach in this planning uses many programs, including Google Earth for determining the coordinates, Global Mapper for obtaining the site contour, and Autocad® Civil 3D for concluding the horizontal alignment. The process of designing with Autocad® Civil 3D is one of the results of this planning.